A novel N-phase multi-modular series HVDC tap - Tang, Yunpeng (2017)
High-voltage direct-current (HVDC) transmission has higher efficiency and lower expenses for the long-distance bulk-power transmission. A HVDC tap is one type of the multi-terminal HVDC systems which transfers a small amount of power from the HVDC line to the nearby communities with no access to the electricity. Developed from the 1960s, HVDC taps can be summarised into series taps and parallel taps, between which series taps are considered to be more promising on the use of devices and the cost. The conventional series taps have some evident drawbacks, which a modular multilevel based series tap may overcome. Here a novel n-phase Multi-Modular Series HVDC Tap (MMST) is proposed to realise the utilisation of the modular multilevel structure into the series tap and improve the performance of typical series taps. In this PhD thesis the theoretical analysis and the parameter design of two-phase and three-phase MMSTs based on the South-West HVDC Link in Sweden have been carried out. The control strategy for the n-phase MMST, including the load current control, the mean capacitor voltage control and the DC link voltage control, has been designed. In order to verify the feasibility of the proposed topology and the validity of the presented control strategy, simulations have been validated using a low power prototype. The simulation and experimental results indicate that the MMST offers better performance when compared to the conventional series taps.